Dual-transgenic BiFC vector systems for protein-protein interaction analysis in plants - Chen, Piaojuan; Ye, Meiling; Chen, Yadi; Wang, Qin; Wang, Qiongli; Zhong, Ming (Frontiers in Genetics, 2024)
Protein-protein interaction (PPI) play a pivotal role in cellular signal transduction. The bimolecular fluorescence complementation (BiFC) assay offers a rapid and intuitive means to ascertain the localization and interactions of target proteins within living cells. BiFC is based on fluorescence complementation by reconstitution of a functional fluorescent protein by co-expression of N-and Cterminal fragments of this protein. When fusion proteins interact, the N-and C-terminal fragments come into close proximity, leading to the reconstitution of the fluorescent protein. In the conventional approach, the N-terminal and C-terminal fragments of the fluorescent protein are typically expressed using two separate vectors, which largely relies on the efficiency of the transformation of the two vectors in the same cells. Furthermore, issues of vector incompatibility can often result in loss of one plasmid. To address these challenges, we have developed novel dual-transgenic BiFC vectors, designed as pDTQs, derived from the previously published pDT1 vector. This set of BiFC vectors offers the following advantages: (1) Both fluorescent fusion proteins are expressed sequentially within a single vector, enhancing expression efficiency; (2) Independent promoters and terminators regulate the expression of the two proteins potentially mitigating vector compatibility issues; (3) A long linker is inserted between the fluorescent protein fragment and the gene of interest, facilitating the recombination of the fused fluorescent protein into an active form; (4) Four distinct types of fluorescent proteins, namely EYFP, mVenus, mRFP1Q66T and mCherry are available for BiFC analysis. We assessed the efficiency of the pDTQs system by investigating the oligomerization of Arabidopsis CRY2 and CRY2-BIC2 interactions in N. benthamiana. Notably, the pDTQs were found to be applicable in rice, underscoring their potential utility across various plant species.